Spatial location of place-based subsidized households and uneven geography of opportunities: case of Austin, Texas in the US. Issue 1 (1st January 2016) - Woo, Ayoung; Kim, Young-Jae
Abstract: As an alternative to traditional public housing programs, the Low-Income Housing Tax Credit (LIHTC) program has been the dominant federal affordable housing program in the US. However, we have empirically limited understanding as to whether the LIHTC program promotes locational options that offer better socioeconomic opportunities for low-income families. This paper examines the relationships between the spatial location of public housing and LIHTC households and sociodemographic characteristics of neighborhoods in Austin, Texas. We find that both public housing and LIHTC households are located in disadvantaged neighborhoods, especially in terms of higher minority populations, poverty, unemployment, female-headed family, welfare receipt, teenage school dropouts, and lower income. Furthermore, our study shows that the location of public housing and LIHTC households is associated with concentrated crime. However, after accounting for the geographic and sociodemographic characteristics of neighborhoods, only neighborhoods where LIHTC households are located are significantly related to concentrated crime incidents.